2013
DOI: 10.1038/ismej.2013.125
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomically and functionally diverse microbial communities in deep crystalline rocks of the Fennoscandian shield

Abstract: Microbial life in the nutrient-limited and low-permeability continental crystalline crust is abundant but remains relatively unexplored. Using high-throughput sequencing to assess the 16S rRNA gene diversity, we found diverse bacterial and archaeal communities along a 2516-m-deep drill hole in continental crystalline crust in Outokumpu, Finland. These communities varied at different sampling depths in response to prevailing lithology and hydrogeochemistry. Further analysis by shotgun metagenomic sequencing rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
142
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(157 citation statements)
references
References 39 publications
12
142
3
Order By: Relevance
“…(mg/L) ME-7 The bacterial clone analysis results suggested that shared OTUs between samples were less and 168 in 201 OTUs were unique to each sample, showing same result as previous studies [4,16]. Meanwhile, some sequences, closely related to taxa involved in various metabolic processes, were simultaneously found in a single sample (Fig.…”
Section: Correlation Between Bacterial Distribution and Hydrochemicalsupporting
confidence: 81%
See 1 more Smart Citation
“…(mg/L) ME-7 The bacterial clone analysis results suggested that shared OTUs between samples were less and 168 in 201 OTUs were unique to each sample, showing same result as previous studies [4,16]. Meanwhile, some sequences, closely related to taxa involved in various metabolic processes, were simultaneously found in a single sample (Fig.…”
Section: Correlation Between Bacterial Distribution and Hydrochemicalsupporting
confidence: 81%
“…Microorganisms in the aquifer have to develop adaptation mechanisms for survival under oligotrophic conditions in a subsurface environment. Thus, geochemical conditions and particularly availability of electron donors and acceptors are major drivers of microbial composition and diversity in groundwater and geological substratum [3,4]. Additionally, the groundwater system displays pronounced spatial heterogeneity, as a result of the stratified nature of many subsurface deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Of the viral contigs, 86% belonged to members of the Caudovirales, tailed dsDNA viruses, with Myoviridae (44%) and Siphoviridae (26%) families predominating. Previously, only viral reads and prophage genome fragments have been reported 10,26,27 . We mined our microbial genomes for the presence of CRISPRCas systems (clustered regularly interspaced short palindromic repeat-CRISPR associated), which act as an acquired immunity to viruses 28 (Supplementary Table 8).…”
Section: Active Viral Predation In the Deep Subsurfacementioning
confidence: 99%
“…In oligotrophic systems, subsurface lithoautotrophic microbial ecosystems (SLiMEs) (1) that are fueled by H 2 support the occurrence of autotrophic methanogens, acetogens, and sulfate reducers (2)(3)(4)(5). These environments can host highly diverse communities, consisting mostly of prokaryotes, but also multicellular microeukaryotes and viral particles (6)(7)(8)(9)(10)(11)(12)(13). Due to the limitation of available nutrients and energy substrates in the oligotrophic subsurface, it is reasonable to hypothesize that subsurface inhabitants with diverse functional traits cooperate syntrophically to maximize energy yield…”
mentioning
confidence: 99%